2017
DOI: 10.1016/j.cub.2017.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Vocal Diversity through Morphological Adaptation without Vocal Learning or Complex Neural Control

Abstract: SUMMARY The evolution of complex behavior is driven by the interplay of morphological specializations and neuromuscular control mechanisms [1–3], and it is often difficult to tease apart their respective contributions. Avian vocal learning and associated neural adaptations are thought to have played a major role in bird diversification [4–8], whereas functional significance of substantial morphological diversity of the vocal organ remains largely unexplored. Within the most species rich order, Passeriformes, ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Therefore, future work will have to test whether the dramatic efficiency advantage of a syringeal position is maintained for various syrinx designs or if other variables emerge as the main targets of selection. Syrinx morphology shows remarkable diversity, including features such as multiple sound sources [53], multilayered vocal fold design [41], or changes in vocal tract design and motility [32]. All of these features affect efficiency, and we do not know how they are influenced by trade-offs between vocal efficiency and those other acoustic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future work will have to test whether the dramatic efficiency advantage of a syringeal position is maintained for various syrinx designs or if other variables emerge as the main targets of selection. Syrinx morphology shows remarkable diversity, including features such as multiple sound sources [53], multilayered vocal fold design [41], or changes in vocal tract design and motility [32]. All of these features affect efficiency, and we do not know how they are influenced by trade-offs between vocal efficiency and those other acoustic features.…”
Section: Discussionmentioning
confidence: 99%
“…In a third study, we investigated the effect of tracheal length on sound production by a syrinx in situ. The approach of the in situ syrinx has been proven effective [11,5053]. It is important to perform these experiments in situ because excised syringeal preparations may reveal unnatural vibratory behavior of the labia [54].…”
Section: Methodsmentioning
confidence: 99%
“…In the domain of vocal production, vocal output is typically and reasonably thought to be controlled by a network of CPGs [ 6 11 ]; in some species, these CPGs may be activated, modulated, or suppressed by forebrain structures [ 12 14 ] (see [ 15 ] for a recent review). With regard to morphological computation, studies of birds [ 16 18 ], bats [ 19 ], and humans [ 20 ] reveal that the biomechanical properties of the larynx (or syrinx in birds) can simplify motor control of vocal production. For example, in zebra finches, discretely different song syllables can be produced by a simple linear driving force exploiting the soft tissue properties of the syrinx [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The infrequency of complex vocal learning might be due to anatomical constraints. Specifically, it has been suggested that loss of air sacs and the presence of a permanently descended larynx in humans and additional intrinsic syrinx muscles in songbirds are required for flexible modifications of vocalizations (Fitch, 2018;Garcia et al, 2017). However, it has been shown that many vocal non-learning mammals descend their larynx as well when vocalizing.…”
Section: Constraintsmentioning
confidence: 99%
“…More likely, the descended larynx evolved to produce lower-formant frequencies, to acoustically exaggerate size (Fitch, 2018). With respect to birds, it has been found that syrinx muscle complexity does not correlate with vocal learning, but rather allows a vocal non-learner to produce a greater variety of innate sounds (Garcia et al, 2017). Finally, the larynx of a nonhuman monkey has been shown to be speech ready, indicating that the long-held view that vocal organ morphology is the culprit for the lack of complex vocal learning in nonhuman primates is incorrect (Fitch et al, 2016).…”
Section: Constraintsmentioning
confidence: 99%